Adducts to DNA - Bartsch, Helmut (Encyclopedic reference of cancer, 2001)
• macromolecule-bound carcinogens DNA-bound carcinogen adducts reflect the amount of a chemical that covalently interacts with nucleic acid bases at the target site (biologically active dose) or in surrogate tissues.